"The Sun Came Up Because You Got Here…": A Qualitative Exploration of Person-Centered Care Strategies Used by Adult Day Care Centers to Manage Behavioral and Psychological Symptoms of Dementia. (February 2023) - Boafo, Jonelle; David, Daniel; Wu, Bei; Brody, Abraham A.; Sadarangani, Tina
In order to reduce care partner strain and support aging in place for people living with Alzheimer's Disease and Alzheimer's Disease Related Dementias (AD/ADRD), adult day centers (ADCs) must manage behavioral and psychological symptoms of dementia (BPSD). The purpose of this paper is to identify person-centered care strategies used by center staff to manage BPSD. Six focus groups with center staff (n = 31) were conducted. Data were analyzed using directed content analysis guided by Kitwood's conceptual approach to cultivating personhood in dementia care. Themes were identified and organized within Kitwood's framework. The results demonstrate that staff incorporate evidence-based person-centered approaches to AD/ADRD care that align with Kitwood's principles of comfort, attachment, inclusion, and identity. Staff individualize their approach to people with AD/ADRD within a group setting. They monitor, engage, socially stimulate, and, when needed, de-stimulate them. Centers are flexible social environments with underrecognized expertise managing BPSD using person-centered approaches.